Effect of quality of radiographs taken during root canal treatment on technical quality of root canal fillings and endodontic outcome - Jia Min Ng; Yan Yee Lee; Prashanti Chippagiri; Elaheh Ahanin; Abhishek Parolia (Restorative Dentistry & Endodontics, 2025)
Objectives This study evaluated the number and quality of working length (WL) and master cone (MC) radiographs taken during root canal treatment by dental undergraduates, and their associations with the technical quality of root canal fillings (TQRCF) and endodontic outcomes (EO). Methods A retrospective evaluation of radiographs from 303 root canal-treated teeth in 231 patients was conducted, with 72 patients attending recall visits to assess EO. The chi-square and one-way analysis of variance tests were performed. Results A total of 505 WL and 557 MC radiographs were reviewed, with 72.9% and 75% deemed satisfactory, respectively. Satisfactory TQRCF was achieved in 60.4% of cases. Significant associations were found between the extension of the file in WL and gutta-percha in MC radiographs and TQRCF (p = 0.000). Misinterpretation of these radiographs resulted in poor TQRCF. Furthermore, 64.2% of teeth had satisfactory EO. A significant relationship was noted between the quality of MC radiographs and both TQRCF (p = 0.043) and EO (p = 0.003). Conclusions Unsatisfactory MC radiographs were linked to poor TQRCF and unfavorable EO. Regular radiographic training is recommended to enhance EO.